154k views
0 votes
10. Solve:6 - 2(x + 6) = 3x +4
x = -2
x = 2
x=-10
x = 10

User Juhyun
by
4.8k points

2 Answers

1 vote

Answer:

x = -2

Explanation:

6 - 2(x + 6) = 3x + 4

Step 1: Multiply -2(x+6)

6 - 2(x + 6) = 3x +4

6 - 2x - 12 = 3x + 4

Step 2: Distribute the left side ("6 - 2x - 12")

-2x - 6 = 3x + 4

Step 3: Add "-2x" to both sides.

-2x - 6 = 3x + 4

+2x +2x

-6 = 5x + 4

Step 4: Subtract "4" from both sides.

-6 = 5x + 4

-4 -4

-10 = 5x

Step 5: Divide both sides by "5" to get x alone.

-10 = 5x

5 5

x = -2

User Thibaut Noah
by
4.7k points
5 votes

Answer:

x = -2

Explanation:

6 - 2(x + 6) = 3x +4

6 -2x - 12 = 3x + 4

6 - 12 - 2x = 3x + 4

-6 -2x = 3x +4

-6 - 4 - 2x = 3x + 4 - 4

-10 -2x = 3x

-10 -2x + 2x = 3x + 2x

-10 = 5x

-10 / 5 = 5x/5

x = -2

I hope this helps!!

User InfiniteRefactor
by
5.4k points